The effects of drugs on Onchocerca volvulus: 2. The antimonial preparations TWSb and MSbE - Duke, B. O. L. (1968)
Antimonial preparations (Pentostam, Neostibosan, stibophen, and tartar emetic) have occasionally been used in the treatment of onchocerciasis without very promising results. The advent of the preparations TWSb (stibocaptate) and MSbE (Friedheim) of allegedly reduced toxicity made it desirable to test them against Onchocerca volvulus. The action of both preparations on the parasites was found to vary from one patient to another, ranging from complete elimination of all parasites in a few cases to no detectable action in others. A microfilaricidal action was detectable in many patients, particularly after treatment with TWSb, which was used at higher doses than MSbE. A lethal or sterilizing action on some or all adult female worms was observed in some patients. However, toxic reactions to the drugs were common and distressing, and often it was necessary to stop treatment on this account. Anorexia, nausea, vomiting and prostration were the most common manifestations, and there was one fatality from coincident yellow fever, which may well have been aggravated by antimony treatment. The uncertain action of these preparations on O. volvulus and the toxic manifestations that accompany their use render them unsuitable for the treatment of onchocerciasis, and it is probable that the effects of antimony on O. volvulus are produced only at or above the normal level of human tolerance.